Simulasi Traffic Light Persimpangan 4 Arah untuk Optimasi Alur Kendaraan Menggunakan Programmable Logic Controller (PLC) Omron CP1L - Sabda Dwi Arvinda; Elpi Purnamasari; Aldi Fadilla Ramadhan; Ardian Sah; Didik Aribowo (Jurnal Penelitian Rumpun Ilmu Teknik, 2025)
Traffic congestion is a major challenge in many big cities, including Serang City, Banten Province. This study aims to optimize vehicle flow at a four-way intersection using a traffic light system based on Omron CP1L Programmable Logic Controller (PLC). The research method involves simulation and hardware experiments to analyze traffic efficiency. The simulation results show that the PLC system can adjust the duration of traffic lights based on vehicle density, thereby reducing queues and increasing vehicle flow efficiency. This study concludes that the PLC-based approach is effective for more dynamic traffic management and recommends further improvements to the design aspects of indicator lights to ensure signal clarity for road users.